2018
DOI: 10.1016/j.jecp.2017.09.008
|View full text |Cite
|
Sign up to set email alerts
|

What drives young children to over-imitate? Investigating the effects of age, context, action type, and transitivity

Abstract: Imitation underlies many traits thought to characterize our species, which includes the transmission and acquisition of language, material culture, norms, rituals, and conventions. From early childhood, humans show an intriguing willingness to imitate behaviors, even those that have no obvious function. This phenomenon, known as "over-imitation," is thought to explain some of the key differences between human cultures as compared with those of nonhuman animals. Here, we used a single integrative paradigm to si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 65 publications
(95 reference statements)
1
14
0
1
Order By: Relevance
“…found that children imitated more faithfully when they were told that the action represented a social convention. Similar results were later found by Clay, Over & Tennie (2018) who tested 4-to 6-year-old British children and found that the older children in their sample were more likely to copy the modelled actions faithfully when these actions had been framed as a social convention.…”
Section: Adherence To Normssupporting
confidence: 78%
“…found that children imitated more faithfully when they were told that the action represented a social convention. Similar results were later found by Clay, Over & Tennie (2018) who tested 4-to 6-year-old British children and found that the older children in their sample were more likely to copy the modelled actions faithfully when these actions had been framed as a social convention.…”
Section: Adherence To Normssupporting
confidence: 78%
“…Overimitation satisfies social motives, be they affiliative or normative . For example, in one study , 4‐ to 5‐year‐olds sat opposite two adults.…”
Section: Social Motivesmentioning
confidence: 99%
“…Lyons et al (2007) conclude, "children who observe an adult intentionally manipulating a novel object have a strong tendency to encode all of the adult's actions as causally meaningful" (p. 19,751). Recently, Clay et al (2018) showed that over the course of early development, children move from roundly overimitating to selectively overimitating. Together, this evidence supports the argument for increased preparation of the motivation to imitate in humans; a prepared tendency to imitate first and then refine the deployment of imitation at later ages (also see Flynn et al 2016).…”
Section: Evidence For Preparedness In Imitationmentioning
confidence: 99%